ZnO-nanorods Promoted Synthesis of α-amino Nitrile Benzofuran Derivatives using One-pot Multicomponent Reaction of Isocyanides - Najar, Asef H.; Hossaini, Zinatossadat; Abdolmohammadi, Shahrzad; Zareyee, Daryoush (Combinatorial Chemistry & High Throughput Screening, 2020)
Aims and Objective: In this work ZnO-nanorod (ZnO-NR) as reusable catalyst promoted Strecker-type reaction of 2,4-dihydroxyacetophenone, isopropenylacetylene, trimethylsilyl cyanide (TMSCN), primary amines and isocyanides at ambient temperature under solvent-free conditions and produced α-amino nitriles benzofuran derivatives in high yields. These synthesized compounds may have antioxidant ability. Materials and Methods: ZnO-NRs in these reactions were prepared according to reported article. 2,4-dihydroxyacetophenone 1 (2 mmol) and isopropenylacetylene 2 (2 mmol) were mixed and stirred for 30 min in the presence of ZnO-NR (10 mol%) under solvent-free conditions at room temperature. After 30 min, primary amine 3 (2 mmol) was added to the mixture gently and the mixture was stirred for 15 min. After this time TMSCN 4 (2 mmol) was added to the mixture and stirred for 15 min. After completion of the reaction, as indicated by TLC, isocyanides 5 was added to mixture in the presence of catalyst. Results: In the first step of this research, the reaction of 2,4-dihydroxyacetophenone 1, isopropenylacetylene 2, methyl amine 3a, trimethylsilyle cyanide 4 and tert-butyl isocyanides 5a was used as a sample reaction to attain the best reaction conditions. The results showed this reaction performed with catalyst and did not have any product without catalyst after 12 h. Conclusion: In conclusion, we investigate multicomponent reaction of 2,4-dihydroxyacetophenone 1, isopropenylacetylene 2, primary amines 3, trimethylsilyl cyanide 4 and isocyanides along with ZnO-NRs as reusable catalyst at room temperature under solvent-free conditions which generates α-amino nitrile benzofuran derivatives in high yields. The advantages of our method are high atom economy, green reaction conditions, higher yield, shorter reaction times, and easy work-up, which are in good agreement with some principles of green chemistry. The compounds 8c exhibit excellent DPPH radical scavenging activity and FRAP compared to synthetic antioxidants BHT and TBHQ.
Keywords: Strecker reaction